Reliability of Water Supply Networks - I. Guzynin, Alexander; A. Guzynin, Alexander; ., . (International Journal of Engineering and Technology, 2018)
The reliability of ring water supply networks is investigated. Oriented graphs of annular water supply networks are considered. The structural reliability of such networks is determined. For these purposes, it is suggested to use the method of minimal paths and minimal sections in an oriented graph. This makes it possible to obtain an upper and lower reliability limit for water networks of arbitrary configuration with different diameters and lengths of sections. Using minimal paths and minimal cross-sections, equations are obtained for the reliability of annular water supply networks. For any water supply network, functions can be recorded that determine its actual reliability.Â Â Â